Secondary Bacterial Infections in Patients With Viral Pneumonia - Manohar, Prasanth; Loh, Belinda; Nachimuthu, Ramesh; Hua, Xiaoting; Welburn, Susan C.; Leptihn, Sebastian (Frontiers in Medicine, 2020)
Pulmonary diseases of viral origin are often followed by the manifestation of secondary infections, leading to further clinical complications and negative disease outcomes. Thus, research on secondary infections is essential. Here, we review clinical data of secondary bacterial infections developed after the onset of pulmonary viral infections. We review the most recent clinical data and current knowledge of secondary bacterial infections and their treatment in SARS-CoV-2 positive patients; case reports from SARS-CoV, MERS-CoV, SARS-CoV2 and the best-studied respiratory virus, influenza, are described. We outline treatments used or prophylactic measures employed for secondary bacterial infections. This evaluation includes recent clinical reports of pulmonary viral infections, including those by COVID-19, that reference secondary infections. Where data was provided for COVID-19 patients, a mortality rate of 15.2% due to secondary bacterial infections was observed for patients with pneumonia (41 of 268). Most clinicians treated patients with SARS-CoV-2 infections with prophylactic antibiotics (63.7%, n=1901), compared to 73.5% (n=3072) in all clinical reports of viral pneumonia included in this review. For all cases of viral pneumonia, a mortality rate of 10.9% due to secondary infections was observed (53 of 482). Most commonly, quinolones, cephalosporins and macrolides were administered, but also the glycopeptide vancomycin. Several bacterial pathogens appear to be prevalent as causative agents of secondary infections, including antibiotic-resistant strains of Staphylococcus aureus and Klebsiella pneumoniae.